COSMO-RS Calculations of Partition Coefficients: Different Tools for Conformational Search - Buggert, Matthias; Cadena, Cesar; Mokrushina, Liudmila; Smirnova, Irina; Maginn, Edward J.; Arlt, Wolfgang (Chemical Engineering & Technology, 2009)
This work is encouraged by the growing interest and recent success of quantum mechanics-based methods in modeling of thermodynamic properties in the field of chemical engineering and life sciences. Among those, the COSMO-RS model has become one of the most popular methods to predict phase equilibria in complex bio-related systems. Recently, we have shown that the quality of predictions of n-octanol/water and micelle/water partition coefficients is improved when the weighted mixtures of conformers are used to represent molecules, thereby demanding that the conformation analysis is performed for each component of the system. In this paper, different methods for performing the conformational search are evaluated. Micelle/water partition coefficients of solutes from different homologous series in aqueous solutions of Triton X100 as well as the n-octanol/ water partitioning of three common drugs (aminopinicillanic acid, ampicillin, and penicillin G) are calculated and compared with experimental data. Conformational analysis is made by the HyperChem program for the molecules placed in vacuum as well as by using the molecular dynamics simulation in a solvent medium (n-octanol and water). It is demonstrated that molecular dynamics simulation is a promising tool to conduct conformational analysis. Along with the possibility of providing the conformers for large Surfactant and pharmaceutical molecules, the method accounts for the solvent in a realistic manner. The results for micelle/water partition coefficients illustrate that n-octanol is a reasonable approximation for the "micelle-like" medium in molecular dynamics (MD) simulations. Predicted n-octanol/water partition coefficients of three penicillins are in a good agreement with literature data and values Calculated by a common quantitative structure-activity relationship (QSAR).
Keywords: Conformation; COSMO-RS; Drug; Molecular dynamics; Octanol/water and micelle/water partition coefficients